PIRRIST: Patient and public involvement (PPI) to enhance recruitment and retention in surgical trials - Crocker, JC; Bostock, J; Treweek, S; Farrar, N; Chant, A; Cook, JA; Kerr, P; Rees, S; Locock, L; Woolfall, K; Olszowski, S; Bulbulia, R (BMC, 2019)
Meeting abstract from the 5th International Clinical Trials Methodology Conference (ICTMC 2019) https://ictmc2019.com/